ANALYSIS OF MAIN REASONS FOR MISTAKES IN DIAGNOSTICS OF EPILEPTIC SEIZURES AND EPILEPTIC SYNDROMES (CLINICAL PECULIARITIES OF EPILEPTIC SEIZURES) - M. B. Mironov (Russkij Žurnal Detskoj Nevrologii, 2015)
Epilepsy is a chronic brain disease that requires long therapy and continuous careful supervision of the status of the patient. In connection with this, both overdiagnosis and underdiagnosis of this disease is extremely dangerous. Overdiagnosis causes ungrounded social "label", limitation in rights, significant decreasing quality of life of the patient, family problems, prescription of long-term anti-epileptic therapy that may cause potential side effects. Underdiagnosis of epilepsy frequently causes further resistance of seizures to therapy, they become more frequent, there appears the possibility of development of epileptic status, life threatening situations, possibility of development of cognitive disorders associated with the disease. A significant progress in epileptology and medical technologies (video electroencephalographic (EEG) monitoring, neuroimaging methods, genetic studies) that has been marked in recent decades has allowed minimizing errors of physicians. Despite this, certain difficulties still remain in diagnostics of epilepsy. In the author's opinion, there is a range of epileptic seizures visual assessment of which is extremely difficult and is literally impossible without video EEG monitoring. Short, phantom, atypical absences, absences on the outside, epileptic myoclonus of the eyelids with or without absences, myoclonic, tonic, gelastic, focal hyperkinetic seizures, epileptic aura, reversing focal seizures, epileptic spasms, ictal syncopes, negative myoclonus, focal epileptic myoclonus, epileptic seizures arising when closing the eyes, and self-induced seizures can be attributed to such seizures with difficulties in diagnosis. The author reviews each of these types epileptic seizures in details focusing the attention on their diagnostic criteria and characteristics of the clinical and the EEF features that are of utmost importance in the course of performance of differential diagnostics. Own experience of the author and data of literature show that one should perform final interpretation of paroxysmal states only after video EEG monitoring for the purpose of minimizing diagnostic errors.